Optimized design method for grid-current-feedback active damping to improve dynamic characteristic of LCL-type grid-connected inverter. (September 2018) - Chen, Yandong; Xie, Zhiwei; Zhou, Leming; Wang, Zili; Zhou, Xiaoping; Wu, Wenhua; Yang, Ling; Luo, An
Graphical abstract: Highlights: A virtual impedance equivalent model is established. An optimized design method for grid-current feedback active damping is proposed. Analyzed the relationship of system characteristics and damping control parameters. Abstract: In LCL-type grid-connected inverter, an optimized design method for grid-current-feedback active damping (AD) is proposed to improve the system dynamic characteristic. By analyzing the equivalent virtual impedance model, the essential relationship between the system dynamic characteristic indicators and damping control parameters is obtained, and the damping control parameters are contradictory that difficult to optimize. Then, a parameters optimization design method combining zero-pole model and Routh stability criterion is proposed to reduce the complexity of the parameters design and improve the system dynamic. Moreover, the influence of the control delay on system stability and parameters design is analyzed in the discrete domain. Simulation and experimental results verified the validity of the proposed method.